Geo-Texas a guide to the earth sciences - Swanson, Eric R. (Texas A & M Univ. Press, 1995)
Geo-Texas succeeds in bringing together astronomy, geology, meteorology, oceanography, and environmental studies in a highly informative, on-of-a-kind guide to earth sciences in the Lone Star State.
Keywords: Earth sciences -- Texas; Geologie; Texas